Compliments and Refusals in Poland and England - Bhatti, Joanna; Žegarac, Vladimir (Research in Language, 2012)
There are significant cross-cultural differences in the way compliments and refusals are made and responded to. The investigation of these speech acts touches on some interesting issues for pragmatic theory: the relation between the universal and the culture-specific features of complimenting and refusing, the importance of culture specific strategies in explaining how these speech acts are produced and responded to, as well as the relation between the message conveyed by a compliment or refusal and its affective/emotional effects on the hearer. The pilot study presented in this paper investigates the production and reception of compliments and refusals in the relatively proximate cultures of England and Poland. The findings reveal significant systematic cross-cultural differences relating to refusals, while the differences relating to compliments are fewer and more subtle. The data suggests that the cross-cultural similarities and differences observed can be explained in terms of (a) a universalist view of institutional speech acts and face concerns in rapport management, (b) the Relevance-theoretic view of communication and cognition as oriented towards maximising informativeness and (c) some culture-specific values. These tentative conclusions are based on very limited data and indicate useful directions for future research.